A rare I2O3 hybrid organic–inorganic material with high connectivity and quadruple-stranded helices1. Issue 7 (21st February 2015) - Yang, Gao-Shan; Liu, Chong-Bo; Wen, Hui-Liang; Tan, Sheng-Shui; John Zhang, Z.
<x xml:space="preserve">Abstract</x> A novel I2O3 hybrid material with one Cd–OH helix, two quadruple-stranded Cd–ligand helices and a (5, 14-c) topological net was assembled.